Idiopathic thrombocytopenic purpura: laboratory diagnosis and management - Alvina, Alvina (Universa Medicina, 2011)
Idiopathic thrombocytopenic purpura (ITP) or immune thrombocytopenic purpura is a disease characterized by low platelet count (<150,000/ìL) caused by autoantibody-mediated platelet destruction and the absence of other causes of thrombocytopenia. Acute primary ITP is more common in children 2-6 years of age, with similar incidence between males and females, while the chronic form is usually encountered in adults with median age of 40-45 years. The clinical signs of ITP are purpura, ecchymosis, petechiae and gastrointestinal tract bleeding, gingival bleeding, epistaxis, and urinary tract bleeding. Spontaneous mucosal, intracranial, and gastrointestinal hemorrhage may occur at platelet counts of <10000/ìL. To date, the diagnosis of ITP is still arrived at by exclusion, i.e. by elimination of other causes of thrombocytopenia. The diagnosis of ITP also requires a medical history (anamnesis), physical examination, platelet count, and examination of a peripheral blood smear. The latter examination in ITP shows low numbers of normal-sized platelets, occasionally also giant platelets, while erythrocytes and leukocytes have a normal morphology. The bone marrow is usually normal or shows increased megakaryocytes. Assessment of antithrombocyte antibody may assist in establishing the diagnosis of ITP. Management of ITP is based on platelet count and severity of bleeding. Treatment is aimed at interfering with antibodies that damage the platelets, by inhibiting the functions of macrophage Fcã receptors and decreasing the production of antiplatelet antibodies. Thrombopoietin (TPO) receptor agonists including eltrombopag and romiplostim have offered an important new option in treating ITP.